2012
DOI: 10.5507/bp.2012.021
|View full text |Cite
|
Sign up to set email alerts
|

Protobothrops mangshanensis bite: first clinical report of envenoming and its treatment

Abstract: Aim. This case report presents envenoming by the Chinese pit viper Protobothrops mangshanensis (formerly Zhaoermia) and its treatment. Methods. A 38 year old snake breeder suffered two-fang bites to elbow by a Chinese pit viper Protobothrops mangshanensis resulting in local edema of the affected arm. No other signs of envenoming appeared. On the 5 th day following the bite a hematoma developed on the other arm which had been mechanically injured 14 days before. Laboratory testing revealed severe coagulopathy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…and Protobothrops sp. [8,9,19,28,35,40]. An in vivo study using TAAV against the heterologous venoms of four Indonesian Trimeresurus species confirmed that the closer phylogenetic relationship of interspecific snakes provided better cross-neutralizing capacity [28].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…and Protobothrops sp. [8,9,19,28,35,40]. An in vivo study using TAAV against the heterologous venoms of four Indonesian Trimeresurus species confirmed that the closer phylogenetic relationship of interspecific snakes provided better cross-neutralizing capacity [28].…”
Section: Discussionmentioning
confidence: 93%
“…Within these validated species, a new distribution of P. mucrosquamatus has been recently reported in Nan Province, northern Thailand [7]. Protobothrops bites have constituted a serious health problem given that its highly hematotoxic venom causes a profoundly delayed coagulopathy, hypofibrinogenemia [8,9], potent hemorrhagic shock effects, acute kidney injury, rhabdomyolysis and fatality [10][11][12]. P. mucrosquamatus has been widely recognized for its high medical importance (Category 1) in China and Taiwan, and moderate medical importance (Category 2) in India, Vietnam, Myanmar (Kachin State) and Laos [13].…”
Section: Introductionmentioning
confidence: 99%
“…bites from other countries show that envenomation may cause many complications similar to those in this case. 7 -10 In this case report, P kelomohy venom could produce both local and systemic effects. The clinical symptoms included suspected compartment syndrome in the bitten limb and systemic involvement, including coagulopathy and rhabdomyolysis, which developed within the first day of the bite, indicating the severity of the venom.…”
Section: Discussionmentioning
confidence: 84%
“…Two cases involving the use of green pit viper antivenom against Protobothrops mangshanensis have been reported. 8,9 These patients had a delay in the onset of complications involving bleeding observed on days 5 and 6 after envenomation. Both cases showed improvement of coagulopathy within 24 h after the first dose of green pit viper antivenom.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the Mangshan pit viper have focused on venom ( Mebs et al, 2006 ; Murakami et al, 2008 ; Valenta, Stach & Otahal, 2012 ), identification of individuals ( Yang et al, 2013 ), and on population status and distribution ( Gong et al, 2013 ). However, little is known about their habitat requirements, which would provide basic information about how the snake meets its needs for survival; therefore, this information is especially crucial in efforts to preserve this at-risk species ( Zhou, 2012 ).…”
Section: Introductionmentioning
confidence: 99%